2010
DOI: 10.1177/0956797610393745
|View full text |Cite
|
Sign up to set email alerts
|

“He Loves Me, He Loves Me Not . . . ”

Abstract: This research qualifies a social psychological truism: that people like others who like them (the reciprocity principle). College women viewed the Facebook profiles of four male students who had previously seen their profiles. They were told that the men (a) liked them a lot, (b) liked them only an average amount, or (c) liked them either a lot or an average amount (uncertain condition). Comparison of the first two conditions yielded results consistent with the reciprocity principle. Participants were more att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Participants who uttered uncertain phrases demonstrated increased curiosity and produced more intense emotional reactions compared with participants who uttered phrases reflecting certainty (Bar Anan et al, 2009). In a second study examining attractiveness using Facebook profiles, uncertainty was manipulated in female college students (Whitchurch, Wilson, & Gilbert, 2010). In the uncertain condition, participants were told that attractive male college students may or may not have liked them.…”
Section: Uncertainty Intensifies Affectmentioning
confidence: 99%
“…Participants who uttered uncertain phrases demonstrated increased curiosity and produced more intense emotional reactions compared with participants who uttered phrases reflecting certainty (Bar Anan et al, 2009). In a second study examining attractiveness using Facebook profiles, uncertainty was manipulated in female college students (Whitchurch, Wilson, & Gilbert, 2010). In the uncertain condition, participants were told that attractive male college students may or may not have liked them.…”
Section: Uncertainty Intensifies Affectmentioning
confidence: 99%
“…The motive for human's behavior for TDMA aligns with the motives proposed by other models of interpersonal relationships. The emphasis on the other person's ability to facilitate the perceiver's goals-and trust that the other person will do so-aligns well with interdependence theory (Kelley, 1979;Rusbult & Van Lange, 2008) and equity theory (Walster, Walster, & Berschied, 1978), among other approaches. This consistency allows for tremendous theoretical integration and refinement, and for testable predictions that extend far beyond the narrow band of phenomena usually considered under the purview of attraction.…”
Section: Theoretical Developmentmentioning
confidence: 65%
“…In the context of rejection in a romantic relationship, anger may result when people feel misled by the rejector's previous statements of trust/commitment (e.g., "I gave you everything because you told me that you loved me!") or when they feel they have invested more in the relationship than the rejector (Walster et al, 1978). Anger is then expressed to recalibrate the social exchange in the perceiver's favor (Sell, Tooby, & Cosmides, 2009).…”
Section: Acceptance Versus Rejectionmentioning
confidence: 99%
“…However, although Whitchurch et al (2011) concluded that uncertainty led to "romantic attraction," their measure was primarily a measure of behavioral intentions. Of their six questions, four were behavioral (interest in class project, friend, hook up with, and potential boyfriend), one was affective (how much do you like), and one is best considered as a precursor to attraction (perception of similarity).…”
Section: Discussionmentioning
confidence: 99%
“…First, a trust-based approach hypothesizes that an individual would select (as an index of behavioral attraction) most frequently a partner associated with certainty of liking, whereas the positive-consequences approach hypothesizes that an individual would select most frequently those persons associated with uncertainty (Hypothesis 1). Second, the trust-based approach posits that uncertainty should not necessarily produce affective attraction, whereas the positive-consequences approach posits that uncertainty produces "romantic attraction," which manifests itself as affective and behavioral attraction (Whitchurch et al, 2011;Hypothesis 2). And third, whereas the positive-consequences approach submits that such behavioral attraction is mediated by romantic desires/interests, the trust-based approach posits that any increase in behavioral attraction is mediated by a motivation to reduce uncertainty (Hypothesis 3).…”
Section: Overview Of the Studiesmentioning
confidence: 99%